Policy Incoherence and Reactive Approaches: Barriers to Effective Management of Land Subsidence in Semarang City, Indonesia - Mohammad Nurul Huda; Renata Jati Nirmala; Irfan Murtadho Yusuf (Faculty of Social and Political Sciences, Universitas Diponegoro, 2024)
Urbanization drives population growth and development in the coastal area of Semarang City, Indonesia, which in turn increases water consumption demand. To meet these demands, massive exploitation of groundwater has become a common practice. Consequently, groundwater reserves are depleting, causing damage to soil composition, particularly in the alluvial land characteristic of the area. These factors contribute to loads that exceed the land's carrying capacity, leading to extreme subsidence rates in Semarang's coastal areas. This research analyzes the obstacles faced by central and regional governments in implementing public policies to mitigate sustainable land subsidence. A qualitative approach with descriptive methods was employed, with a rigid selection of existing literature, journal articles, official documents, and news related to the research topic. The study utilizes a public policy perspective to map and analyze existing literature. The results indicate that handling land subsidence is hindered by several factors: policy incoherency, reactive policy nature, miscoordination among stakeholders, and overlapping public policies. Consequently, policy implementation in Semarang City has not yielded significant results in addressing subsidence. The study highlights the need for central and regional governments to involve business actors in formulating strategies to manage land subsidence effectively. This research contributes to expanding theoretical and practical knowledge on the implementation of land subsidence management policies by local governments in Indonesia's sustainable environmental sector.